Traffic Culture: Law, Morality and Actual Behaviour - Jørgensen, Anette Jerup (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
This paper is about culture of automobility and is based on a qualitative and quantitative enquiry carried out in Northern Jutland, Denmark 2005. The paper presents information about traffic culture in Denmark, theoretical and methodological reflections on traffic safety. The purpose of the paper is to present a sociological view of the Danish traffic culture and it is constructed around three basic issues. The first is how drivers relate to legal standards and moral norms in traffic. The second the possibilities and constraints of legal standards and moral norms to regulate the behaviour of drivers and the final issue is how this influence the risk of traffic accidents among drivers. Since most accidents occur with two or more drivers it is important to bring attention to social patterns of interaction and the ability of normative practises to regulate the behaviour of drivers. It is an almost absent perspective in current research concerning traffic safety.